2016
DOI: 10.1002/art.39528
|View full text |Cite
|
Sign up to set email alerts
|

Combined Pulmonary Fibrosis and Emphysema in Scleroderma‐Related Lung Disease Has a Major Confounding Effect on Lung Physiology and Screening for Pulmonary Hypertension

Abstract: Objective. To assess the prevalence of combined pulmonary fibrosis and emphysema (CPFE) in systemic sclerosis (SSc) patients with interstitial lung disease (ILD) and the effect of CPFE on the pulmonary function tests used to evaluate the severity of SSc-related ILD and the likelihood of pulmonary hypertension (PH).Methods. High-resolution computed tomography (HRCT) scans were obtained in 333 patients with SScrelated ILD and were evaluated for the presence of emphysema and the extent of ILD. The effects of emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 37 publications
5
67
0
Order By: Relevance
“…This syndrome is characterised by the association of severe dyspnoea, paraseptal emphysema and diffuse infiltrative opacities suggestive of pulmonary fibrosis, occurring most often in smokers [23]. As a consequence spirometry is usually normal, contrasting with very severely impaired DLCO and hypoxaemia during exercise (with a major confounding effect on the forced vital capacity/DLCO ratio [24]). Interestingly, this syndrome is associated with a high risk of PH, as identified in more than 50% of patients [23,25].…”
Section: Interstitial Lung Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…This syndrome is characterised by the association of severe dyspnoea, paraseptal emphysema and diffuse infiltrative opacities suggestive of pulmonary fibrosis, occurring most often in smokers [23]. As a consequence spirometry is usually normal, contrasting with very severely impaired DLCO and hypoxaemia during exercise (with a major confounding effect on the forced vital capacity/DLCO ratio [24]). Interestingly, this syndrome is associated with a high risk of PH, as identified in more than 50% of patients [23,25].…”
Section: Interstitial Lung Diseasementioning
confidence: 99%
“…As lung volumes can be normal, it is possible that this syndrome is underdiagnosed in SSc. Recently, ANTONIOU et al [24] showed that emphysema in patients with SSc-related ILD can also be observed in nonsmokers and smokers with a low pack-year history. The significant prevalence of emphysema in nonsmokers with SSc-related ILD provides indirect support for a pathogenetic basis for the CPFE syndrome.…”
Section: Interstitial Lung Diseasementioning
confidence: 99%
“…In SSc, an elevated FVC/DLCO ratio (in essence, the inverse of KCO) was found to be an independent predictor for the presence of PH and is included in the DETECT as an indication for the performance of echocardiography [65]. However, in SSc patients with combined pulmonary fibrosis and emphysema (CPFE), elevation of FVC/DLCO is usual, irrespective of the presence or absence of pulmonary vasculopathy [66]. Use of FVC/DLCO has also been explored in IPF but this variable suffers from measurement variability as three variables must be measured (FVC, KCO and VA) whereas KCO is quantified as a single variable (integrated with VA in the computation of DLCO).…”
Section: Diagnosismentioning
confidence: 99%
“…When considering lung function tests, it is important to consider that concurrent emphysema might reduce the utility of measuring gas exchange (DLCO) in patients for screening as it may increase FVC and diminish DLco independent of pulmonary hypertension. [78,79]. The DETECT cohort included patients with mild PAH and specific determinants of PAH progression have been elucidated using data from this cohort [80] and align with variables such as Nt-pro-BNP and low DLco identified in other cohorts [52,81,82].…”
Section: [H2] Screening and Diagnosis Of Pulmonary Hypertensionmentioning
confidence: 99%